PENGARUH TINGKAT EFISIENSI, RISIKO KREDIT, DAN TINGKAT PENYALURAN KREDIT PADA PROFITABILITAS LEMBAGA PERKREDITAN DESA (LPD) - Indah Lestari, Oka Sri; Suartana, I Wayan (E-Jurnal Akuntansi, 2017)
Lembaga Perkreditan Desa (LPD) is a financial institution owned by the desa pekraman that aims to help desa pekraman in running cultural functions and facilitate the payment traffic so that it can prosper the economic life of the villagers. The purpose of this study was to determine whether the level of efficiency (ROA), credit risk (NPL) and the lending rate (LDR) effect on profitability (ROA) at LPD in Gianyar regency year 2013-2015. This study uses a sample of 519 LPD and data analysis techniques that multiple linear regression with first performed classical assumption. Based on the results of multiple linear regression analysis, note that the results showed variable BOPO significant negative effect on ROA LPD in Gianyar, variable NPL positive effect was not significant to the ROA LPD in Gianyar , while the variable LDR positive significant effect on ROA LPD in Gianyar.
Keywords: The efficiency level, Credit Risk, Level Lending, Lembaga Perkreditan Desa, and LPLPD.